Penilaian Masyarakat Tani di Desa Buyat Terhadap Kinerja Pelayanan Publik Dinas Pertanian Pemerintah Daerah Kabupaten Bolaang Mongondow Timur - silvana . basala (Universitas Sam Ratulangi, 2012)
ABSTRACTSilvana Basala. Society assessment of Buyat Village farmer to thePublic Service performance of Agriculture Department East Bolaang regencyMongondow under the guidance of O.Esry H. Laoh as chairman Ir. JulianaR.Mandei and Celsius Talumingan as a member.The objective of the study to examine the assessment of the farmers in thevillage of Buyat on the performance of public services Agriculture DepartmentEast BolaangMongondow East Regency.The data used are primary data and secondary data, primary data obtainedfrom the farmers in the village of Buyat and secondary data obtained from agenciesor related agencies. Data was collected through direct interviews with the farmersin the village of Buyat. The method of data analysis is descriptive analysis methodpresented in tabular form by calculating the results of the assessment every farmcommunity based services and calculate the results average value of each elementof service.Based Assessment of the Farmers in the village of Buyat on theperformance of the public Department of agriculture Easr Bolaang Mongondowregency, it can be categorized as either. However, there ara still some elements thatare not goo.From both these results indicate that the public service provided by theDepartment of Agriculture Regional BolaangMongondow East Government can besaid to have a poor public services. Therefore, it is expected that the Department ofAgriculture Regional BolaangMongondow East Government to improve theperformance of services to the farming community as well as to pay attention tothe needs of the farmers, and can accept input from a farm community, whether itbe information, advice, opinions, responses, and or complaints.These things should be followed up with efforts to inprove the Departmentof Agriculture service to the farming community. Given that often a time there is adifference between the aspirations of the farmers and the government. And toooften there is a difference of interpretation about the success of a program run bythe government. On the other side often it is assessment that the program issuccess, by the govermant but the reality on the ground is not like what thegovernment hopes.